Clinical Profile of Children with Primary Headache at a Tertiary Care Center in North India: A Retrospective Study - Rahul Sinha; Dharmesh Soneji; Gautam Kamila; Sonali Singh; Ashish Upadhyay (Korean Child Neurology Society, 2023)
Purpose The present study investigated the clinical profile of children with primary headache at a tertiary care center in North India. Methods A retrospective observational study was conducted between January 2021 and October 2022. In total, 100 children 5 to 18 years of age who attended the pediatric outpatient department or the emergency department with primary headache were included. Children with secondary causes of headache were excluded. Results This study included 100 children (40 boys, 60 girls), and the female-to-male ratio was 1.5:1. The patients ranged in age from 5 to 18 years (mean±standard deviation, 10.1±2.8). Migraine headaches were most commonly reported (60%) followed by tension-type headache (28%) and others (12%). The throbbing type of pain was most common (43%), followed by the tightening type in 32%. The pain location was bilateral frontal in 47% of patients, followed by bitemporal in 20% and occipital in 17%. Most of the children (87%) had a headache duration of 2 to 4 hours. The common precipitating factors were skipped meals (25%), bright light (18%), lack of sleep (16%), and schoolwork (15%). A family history was present in around 62%. Around 70% of children required prophylactic medications (flunarizine and propranolol). Long screen time (2 to 4 hours/day) and a family history of headache were significantly associated with primary headache (P<0.05). Conclusion The present study highlights that migraine is most common cause of primary headache in children, and every effort should be made for the early detection and management of headaches among children.